PENGARUH PARIWISATA TERHADAP PERALIHAN FUNGSI TANAH PEKARANGAN DESA (PKD) (STUDI DI DESAPAKRAMAN PADANGTEGAL, UBUD, GIANYAR) - Mendrawan, Gusti Ngurah; Wita, I Nyoman; Atu Dewi, A. A. Istri (Kertha Desa; Vol. 02, No. 02, Mei 2014, 2014)
The land is importan for the society, economic value of land is very high at tourism object area. Customary village of Padang Tegal is famous tourism object with natural environment and its culture. From this background can be formulated the issues as follows: how is position and function of village land (PKD) at customary village of Padangtegal? How is effect of tourism toward function change of village land PKD) at customary village of Padangtegal. The research method have been applied was empirical research that are law research which concepted as emperical symptom which can be seen in reality life. Analysis was conducted in qualitative and presented analysis descriptively. Conclusion of this study as follows: position of land at customary village of Padangtegal practically have very strong position and function of land at customary village of Padangtegal have function of religious. Existence of tourism have effect toward function change of village land (PKD). From function change have effect to public economic and social.
Keywords: tourism, village land (PKD)